PECULIARITIES OF THE APPLICATION OF DECISIONS IN TAX CASES OF THE EUROPEAN COURT OF JUSTICE IN THE REPUBLIC OF POLAND - BABIN, IGOR (Ehrlich’s Journal, 2025)
The article studies the regulatory consolidation of the procedure for applying decisions in tax disputes of the European Court of Justice in the Republic of Poland. The author determined that the decision of the EU Court is part of EU law, which must be complied with by both member states and candidate states prior to accession. After acquiring the status of a candidate country for accession, the problem of applying the decisions of the Court of Justice of the EU became relevant for Ukraine. An analysis of the experience of resolving this issue by member states, including the Republic of Poland, should accelerate Ukraine’s European integration. It has been established that in the Republic of Poland the case law of the European Court of Justice is not an independent source of law, and there is also no separate law regulating the procedure for the application and enforcement of decisions of the Court of Justice of the EU. This issue is regulated by special norms of industry legislation. Regarding decisions of the Court of Justice of the EU in tax cases – special norms of the Tax Ordinance. In fact, the application of decisions in tax disputes of the Court of Justice of the EU is reduced to taking into account the position of the Court of Justice of the EU when issuing general tax consultations by the Minister of Finance of the Republic of Poland, as well as for the resumption of court proceedings in tax cases. The issuance of general tax consultations is carried out on the basis of current tax legislation, taking into account the case law of the Constitutional Tribunal, administrative courts of the Republic of Poland and the Court of Justice of the EU. The reopening of proceedings takes place not only as a result of a court decision in a Polish case, but even if the decision of the Court of Justice of the EU in the case was made in response to a request sent by another Member State. It has been determined that the case law of the Court of Justice of the EU is one of the grounds for changing the interpretations provided by the Minister of Finance if he considers them incorrect. In the case of the case law of the Court of Justice of the EU, as in the case of the decisions of the Constitutional Tribunal, their content means that the Minister of Finance must change his explanations. It has been proven that the impact of the case law of the Court of Justice of the EU on tax authorities and their interpretation of tax rules largely depends on the type and timing of the decision made by it. Thus, on the one hand, there is a complete disregard by the tax authorities of the classical practice of the Court of Justice of the EU and the conclusions arising from it, on the other hand, this is the only court that can quickly and effectively change the position of the Polish tax authorities.